MicroRNA 155:145 ratio as a marker of atherogenic tilt manifested across different age groups and risk factor profiles. (4th February 2022) - Banerjee, A; Roy, D; Mazumdar, H; Karmakar, S; Bhowmik, R; Biswas, N; Roy, A; Dey, S; Manna, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Differential expression of microRNAs is critical in the genesis and progression of atherosclerosis. MiR145 has atheroprotective role through improved homeostasis of smooth muscle cells (SMC). MiR155 is pro-atherogenic due to its suppression of Bcl6, which antagonises NF-κB and modulates macrophages. Purpose: Our purpose was to determine if the differential expression of miR 155 & 145 (expressed as miR 155:145 ratio) across various age groups and risk factor profiles correlates with atherosclerotic cardiovascular disease (ASCVD). Materials and Methods: This observational cross-sectional study was done between Feb"19 & Jan"20 on 108 patients divided equally into 3 age groups: <18, 18-45 & >45yrs. Family history (of ASCVD or risk factors) and risk factor profile were assessed in all 3 groups; and in the latter two, presence or absence of ASCVD was additionally evaluated by coronary angiogram and/or carotid IMT. MiR155 & 145 were measured in all by RT-PCR, & the results were then compared after calculating the ratio. Results: miR 155:145 ratio was significantly increased in <18yrs aged subjects with a positive family history(p = 0.001). Multivariate regression analysis revealed a significant positive correlation of miR155:145 with family history of risk factors or ASCVD in this group(p < 0.001). In the 18-45yrs age group, the miR 155:145 ratio was found to be significantly increased in patients with diabetes(p = 0.037) and significant coronary artery disease(CAD) as determined by Syntax score(p < 0.001). In multivariate regression analysis, a significant positive correlation was found between miR 155:145 and Syntax score(p < 0.001) – a ratio of 155:145 > 1 implied a greater chance of CAD, with increased numerical values correlating with increased severity of disease as evidenced by Syntax score; and a ratio < 1 decreased the chances of significant CAD considerably. A positive association was also discovered for this ratio with hypertension, diabetes, tobacco exposure and a combination of multiple risk factors, but none of them were statistically significant. In the age group of >45 yrs, regression analysis revealed a statistically insignificant positive association of the miR 155:145 ratio with Syntax score, hypertension, dyslipidaemia and a combination of risk factors. Conclusion: MiR 155:145, when >1, can point towards an 'atherogenic tilt', and greater increase in the ratio numerically may denote more severe disease, as indicated by a positive association with Syntax Score. This atherogenic tilt occurs very early in life, even before 18 years with significant family history. Above 18 years, with addition of other risk factors, this tilt is further compounded, and correlated well with Syntax score and such risk factors. Therefore, miR 155:145 ratio may help in identifying the individuals at risk for development of clinically significant CAD and can be utilised for development of future therapeutic strategies as well as prognostication.